Pengaruh Gaya Kepemimpinan, Disiplin Kerja, Lingkungan Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan Studi Pada Pemadam Kebakaran Kota Batu - Adelia, Keysya; Djaelani, Abdul Kodir; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract In the modern era, the demands on the performance of public sector organizations, especially the Fire Service, are getting higher. This study aims to analyze the influence of leadership style, work discipline, work environment, and organizational commitment on the performance of employees of the Batu City Fire Service. This study uses a quantitative method and uses the type of explanatory research, by distributing questionnaires and interviews to obtain 45 respondents, the results of the study are analyzed using multiple regression analysis. The results of the study show that simultaneously, leadership style, work discipline, work environment, and organizational commitment have a significant effect on employee performance. Partially, leadership style, work discipline, work environment, and organizational commitment each have a positive and significant influence on the performance of employees of the Batu City Fire Service. In conclusion, improving the performance of employees of the Batu City Fire Department can be achieved through an increase in effective leadership style, high work discipline, a conducive work environment, and a strong organizational commitment. Keywords : Influence Of Leadership Style, Work Discipline, Work Environment And Organizational Commitment